Overview of Time Management in Nursing Students - Yosep, Iyus; Hikmat, Rohman; Mardhiyah, Ai; Fadilah, Arifah Afkar (GLOBAL HEALTH SCIENCE GROUP, 2024)
Time management is an important skill for nursing students to face complex challenges in their academic and clinical environments. However, although the importance of time management has been widely recognized, there is not yet an adequate understanding of the dynamics of time management in nursing students, especially in the Indonesian academic environment. This study aims to describe the picture of nursing students' time management and to explore factors that may influence their time management. Descriptive research methods were used using the Self-Regulated in Online Learning Questionnaire (SOL-Q) to collect data from 300 nursing students at Padjadjaran University. Teknik sampling yang digunakan adalah purposive sampling. Data analysis used univariate tests. The research results showed that the majority of nursing students had a high level of time management, namely 201 people (67%). However, some students reported a low level of time management, namely 99 people (33%). Factors that influence time management include a busy curriculum load, the demands of clinical practice, and balance between personal and academic life. Factors influencing time management included a dense curriculum, demands of clinical practice, and the balance between personal and academic life. Interventions tailored to address time management challenges should be developed to support students in optimizing their academic and personal responsibilities. The implication of this research is the importance of developing appropriate interventions to help students who experience difficulties in managing their time.